Self-mutilation and its determinants factors: An integrative review (Research, Society and Development, 2021)
The aim of this study was to analyze what has been produced in the national and international scientific literature about determinants factors of self-mutilation. An integrative review was carried out based on the following guiding question: What scientific evidence is being published about self-mutilation and its risk factors? The search took place in four databases and covered articles with available full text, published between 2016 and 2021, in Portuguese, English and Spanish. From the sample of 16 articles, the following results were obtained: family adversity factors, adverse events in childhood, social influence mediated by the internet and previous diagnosis of mental disorder are important determinants factors of self-mutilation in different stages of life. It is concluded that because self-mutilation is a problem of multifactorial origin, it requires intersectoral interventions, holistic care, and amplified clinic. Therefore, as self-mutilation is considered a national and international public health problem, it is necessary to build public policies that contain the growth in the number of cases and promote the prevention of the various forms of this type of violence.